Impact of the adoption of technological innovation on the credit acquisition of rice farmers in Senegal: A propensity score matching technique - Chioma-Akalugo Ogwuike, P.; Obinna Ogwuike, C.; Arouna, A. (Informa UK Limited, 2022)
This paper examines whether the adoption of the ASI thresher technology by rice farmers in the Senegal River Valley increases their access to credit and their creditworthiness through various pathways. Mainly, this study seeks to verify the argument that the adoption of technologies that increase factor productivity and production capacity eventually leads to the ability (and desire) of adopters to borrow more due to enhanced operations and confidence in their ability to repay loans. This paper uses primary data collected from 194 adopters and nonadopters of the ASI thresher in the Senegal River Valley. Four propensity score matching techniques (nearest neighbour, calliper, stratification and kernel) were used to analyze the data and to remove the selection bias due to observable characteristics. The results from the four techniques consistently show that ASI rice thresher adopters borrowed more money (between 194,000 and 432,000 CFA) in comparison to their neighbours who had not adopted the ASI thresher. This study recommends that, in order to move rice system development closer to meeting the Sustainable Development Goals, policymakers and other stakeholders should increase their proactive efforts to promote ASI adoption in Senegal and other rice-producing regions in Africa. The originality of this paper and its contribution to the literature mainly lie in the quantification of the credit farmers gained and the increase in their creditworthiness due to the adoption of a technology.